Vulnerabilidade ao stress e estratégias de enfrentamento de líderes religiosos cristãos - Baptista, Fernanda Siqueira [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Stress is an organism's complex reaction when there is the need to adapt to something good or bad that happens externally. The vulnerability to stress concerns to the probability to react negatively to an event and can occur because of genetic, psychological or social predisposition. Work is one of the social factors capable of generating vulnerability and, in its sense, the religion leader's work may cause damage for being an emotional job. To manage stress it's required the emission of adaptive behaviors, coping strategies, among which stands out to religious leaders, the Religious Spiritual Coping involving the use of religious beliefs and behaviors. This research aimed to identify how the vunerability to stress at work is presented and the Christian religious learder's coping, with their sociodemographic conditions. Attended the research 80 leaders (40 ministers and 40 priests), male, from a Sao Paulo state's country town and its surroundigns, who answered a sociodemographic questionnaire, the State for Vulnerability to Stress at Work and the Scale for Religious Spiritual Coping. The data analysis was performed from the statistic tests Mann-Whitney and the Spearman's correlation. The results showed that 35% of the ministers and 37,5% of the priests had higher work pressure average rate, not being, however, statistically expressive. The main sources of stress were family to the ministers and the priestly office to the priests. The correlational analysis indicated that beliefs have influence on the spiritual religious coping, and the ministers male a higher use of negative coping, while the priests made a higher use of total religious coping. The correlation between the instruments were positive: in the case of the ministers, the 'Positive Coping' with Pressure at Work', and for the priests 'Dissatisfaction with institutional other' to 'Climate and Organizational Functioning'. About the sociodemographic variable, the ministers had...

O stress é uma reação complexa do organismo, quando há necessidade de se adaptar frente a algo bom ou mau que ocorra externa ou internamente. A vulnerabilidade ao stress diz respeito à probabilidade de ser reagir negativamente a um acontecimento e pode ocorrer por predisposição genética, psicológica ou social. O trabalho é um dos fatores sociais capazes de gerar vulnerabilidade e, neste sentido, a ocupação de líderes religiosos pode causar prejuízos, por se tratar de um trabalho emocional. Para administrar o stress é exigida a emissão de comportamentos adaptativos, estratégias de enfrentamento, dentre as quais se destaca, para os líderes religiosos, o Enfrentamento Religioso Espiritual que envolve o uso das crenças e comportamentos religiosos. Esta pesquisa buscou identificar como se apresenta a vulnerabilidade ao stress no trabalho e o enfrentamento de líderes religiosos cristãos, com suas condições sociodemográficas. Participaram 80 líderes (40 pastores e 40 padres), do sexo masculino, de uma cidade do interior Oeste Paulista e seus arredores, que responderam a um questionário sociodemográfico, a Escala de Vulnerabilidade ao Estresse no Trabalho e a Escala de Coping Religioso Espiritual. A análise dos dados foi feita a partir dos testes estatísticos Mann-Witney e correlação de Sperarman. Os resultados mostraram que 35% dos pastores e 37,5% dos padres obtiveram índice médio superior em pressão no trabalho, não sendo, no entanto, estatisticamente significativos. As principais fontes de stress foram a família para os pastores e o ministro para os padres. A análise correlacional indicou que as crenças influíram sobre o enfrentamento religioso espiritual, sendo que os pastores fizeram maior uso de enfrentamento negativo, enquanto os padres maior uso de enfrentamento religioso total. As correlações entre os instrumentos foram positivas: no caso dos pastores, o Enfrentamento Positivo com Pressão no...
Keywords: Stress (Fisiologia); Religião; Psicologia religiosa; Espiritualidade; Stress (Physiology)